FINANCIAL REPORTING OBLIGATION IN ACCORDANCE WITH CAPITAL MARKET LAW: AN ACCOUNTANT DILEMMA - Suwinto Johan; Richard Chandra Adam (Law Review, 2022)
According to article 68 of the Capital Market Law (CM Law) states that accountants registered with the Financial Services Authority (FSA) who examine the financial statements of issuers and other parties carrying out activities in the capital market are required to submit a confidential notification to the FSA within three days at the latest. The things that may be reported are violations committed against the provisions of the CM Law or its implementing regulations; or things that could endanger the financial condition of the institution or the interests of its customers. When performing audit actions, the auditor that supports the stock market faces a conundrum. the conflict between society’s interests and the company’s objectives. This study aims to examine how accountants can report financial reports that are suspected of violating applicable laws and regulations and the accountant’s dilemma between regulators or the public interest and issuers as the party paying accountants according to the agency theory. This research uses normative juridical method. This study concludes that accountants can report to regulators after obtaining written explanations from the directors so that reporting cannot be done as soon as possible. Accountants in providing an opinion have a dilemma. The originality of this study highlights the need for professionalism and independence in those who support the capital market. In the event of a violation, capital market support specialists, including auditors, are required to notify the authorities. The appropriate authorities should be informed of the audit’s preliminary findings.